Overexpression of BdMATE Gene Improves Aluminum Tolerance in Setaria viridis - Ribeiro, Ana P.; de Souza, Wagner R.; Martins, Polyana K.; Vinecky, Felipe; Duarte, Karoline E.; Basso, Marcos F.; da Cunha, Bárbara A. D. B.; Campanha, Raquel B.; de Oliveira, Patrícia A.; Centeno, Danilo C.; Cançado, Geraldo M. A.; de Magalhães, Jurandir V.; et al. (Frontiers in Plant Science, 2017)
Acidic soils are distributed worldwide, predominantly in tropical and subtropical areas, reaching around 50% of the arable soil. This type of soil strongly reduces crop production, mainly because of the presence of aluminum, which has its solubility increased at low pH levels. A well-known physiological mechanism used by plants to cope with Al stress involves activation of membrane transporters responsible for organic acid anions secretion from the root apex to the rhizosphere, which chelate Al, preventing its absorption by roots. In sorghum, a membrane transporter gene belonging to multidrug and toxic compound extrusion (MATE) family was identified and characterized as an aluminum-activated citrate transporter gene responsible for Al-tolerance in this crop. Setaria viridis is an emerging model for C4 species and it is an important model to validate some genes for further C4 crops transformation, such as sugarcane, maize and wheat. In the present work, Setaria viridis was used as a model plant to overexpress a newly identified MATE gene from Brachypodium distachyon (BdMATE), closely related to SbMATE, for aluminum tolerance assays. Transgenic S. viridis plants overexpressing a BdMATE presented an improved Al-tolerance phenotype, characterized by sustained root growth and exclusion of aluminum from the root apex in transgenic plants, as confirmed by hematoxylin assay. In addition, transgenic plants showed higher root citrate exudation into the rhizosphere, suggesting that Al-tolerance improvement in these plants could be related to the chelation of the metal by the organic acid anion. These results suggest that BdMATE gene can be used to transform C4 crops of economic importance with improved aluminum tolerance.